Post-Vaccination Anaphylaxis in Adults: A Systematic Review and Meta-Analysis - Flavia Pennisi; Anna Carole D’Amelio; Rita Cuciniello; Stefania Borlini; Luigi Mirzaian; Giovanni Emanuele Ricciardi; Massimo Minerva; Vincenza Gianfredi; Carlo Signorelli (Vaccines, 2025)
Background/Objectives: Vaccines have been recognized as one of the most effective public health interventions. However, vaccine-associated anaphylaxis, although rare, is a serious adverse reaction. The incidence of anaphylaxis related to non-COVID-19 vaccines in adults remains underreported. This systematic review and meta-analysis aim to estimate the incidence of post-vaccination anaphylaxis across various vaccines in adults. Methods: A comprehensive literature search of PubMed, Embase, Scopus, and Web of Science identified studies on anaphylaxis following vaccination in adults (≥18 years), excluding COVID-19 vaccines. PRISMA 2020 guidelines were followed. The protocol was registered in PROSPERO in advance (ID CRD42024566928). Random-effects and fixed-effects models were used to pool data and estimate the logit proportion, with the logit-transformed proportion serving as the effect size, thereby allowing for the calculation of event rates. Results: A total of 37 studies were included in the systematic review, with 22 studies contributing to the meta-analysis, representing a combined population of 206,855,261 participants. Most studies focused on influenza vaccines (n = 15). Across all studies, 262 anaphylactic cases were reported, with 153 cases related to influenza vaccines, followed by herpes zoster virus vaccines (38 cases) and yellow fever vaccines (29 cases). Td/Tdap vaccine had the lowest rate (0.0001 per 100,000 participants). The overall random-effects model yielded a logit proportion of −10.45 (95% CI: −12.09 to −8.82, p < 0.001), corresponding to an event rate of 2.91 events per 100,000 subjects (95% CI: 0.56 to 14.73). Sensitivity analysis showed a higher incidence for influenza, hepatitis vaccines, and in vulnerable populations. Conclusions: Anaphylaxis following vaccination in adults is rare but varies by vaccine type. Strengthened monitoring and preparedness are essential, especially in non-medical settings, to ensure a rapid response to anaphylaxis and maintain public confidence in vaccination programs.